2023
DOI: 10.1007/s00384-023-04487-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of electroacupuncture for secondary constipation: a systematic review and meta-analysis

Abstract: Objective Secondary constipation refers to constipation that occurs after certain diseases or medications, such as acute stroke or opioids, and the efficacy of electroacupuncture for secondary constipation is controversial. So, this study aimed to explore the efficacy and safety of electroacupuncture for secondary constipation through a meta-analysis and systematic review. Method We retrieved articles from PubMed, Embase, Cochrane Library, Web of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…[15] Previous studies have shown that acupuncture can improve gastrointestinal and neurological symptoms [16,17] and can effectively treat both primary and secondary constipation. [18] Studies have shown that acupuncture can improve PD-related motor symptoms, non-motor symptoms, quality of life, disease progression, reduce the occurrence of adverse events, and reduce the dose of anti-PD drugs. [19] However, some scholars have found that compared with conventional treatment, acupuncture did not have significant differences in the treatment of PD-related constipation.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Previous studies have shown that acupuncture can improve gastrointestinal and neurological symptoms [16,17] and can effectively treat both primary and secondary constipation. [18] Studies have shown that acupuncture can improve PD-related motor symptoms, non-motor symptoms, quality of life, disease progression, reduce the occurrence of adverse events, and reduce the dose of anti-PD drugs. [19] However, some scholars have found that compared with conventional treatment, acupuncture did not have significant differences in the treatment of PD-related constipation.…”
Section: Introductionmentioning
confidence: 99%